2018
DOI: 10.1073/pnas.1805224115
|View full text |Cite
|
Sign up to set email alerts
|

Gain control explains the effect of distraction in human perceptual, cognitive, and economic decision making

Abstract: SignificanceInformation in the world can sometimes be irrelevant for our decisions. A good decision maker should take into account the relevant information and ignore the distracting information. However, empirical observation showed that human decisions are unduly influenced by distracting information. Diverse theories have been proposed to explain the cost that distracters incur during decision making across perceptual, cognitive, and economics domains. Here, we propose a single, unified model that is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 74 publications
3
57
0
Order By: Relevance
“…One central assumption of our model is gain control whereby the spatial average signal is constantly adjusted across temporal frames. Some previous studies also incorporated gain control in their models and successfully accounted for human tendencies 31,52 . Another central assumption is the limited sampling of N elements in estimating spatial average orientation for each frame.…”
Section: Discussionmentioning
confidence: 99%
“…One central assumption of our model is gain control whereby the spatial average signal is constantly adjusted across temporal frames. Some previous studies also incorporated gain control in their models and successfully accounted for human tendencies 31,52 . Another central assumption is the limited sampling of N elements in estimating spatial average orientation for each frame.…”
Section: Discussionmentioning
confidence: 99%
“…This account of decoy effects suggests that it should be possible to identify a simple model that can reproduce the full decoy influence map with parameters that control this repulsive principle, as well as additional degrees of freedom that allow for asymmetric scaling of the attribute values (quality and economy). Our initial modelling focus was informed by previous simulation work suggesting that adaptive gain control might offer a unifying explanation for choice biases (21) as well as the recent proposal of related models for decoy phenomena involving logistic normalisation (20,29). Here, we describe a model variant that offers a clear explanatory framework for the human data reported here.…”
Section: Computational Modellingmentioning
confidence: 99%
“…This allowed us to explore the dimensionality of the data, with a view to asking whether a single principle can explain the ensemble of reported decoy effects. We found that a remarkably simple model, which draws on a computational framework that we have described previously (21), can capture the full decoy influence (RCS) map. Critically, the model suggests that the three canonical decoy effects are not in fact distinct phenomena but fall naturally out of previously described dynamics of attraction and repulsion of decision values towards and away from a reference value given by the mean of available options.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is particularly important when salient distractors are present and interfering with the processing of targets. The interference induced by distractors, so-called “distractibility”, has been shown to link with several key cognitive functions, such as working memory 12 , endogenous and exogenous attention 13 , perceptual and value-based decision 14 , response inhibition 15 , cognitive control 16 . Moreover, atypical distractibility has been discovered in several psychiatry disorders, including ADHD 17 , autism 18 , depression 19 .…”
Section: Introductionmentioning
confidence: 99%